I have the following IVP: $$\begin{cases}y''-2y'+5y = -8e^{-t},\\ \ \\ y(0) = 2\\ \ \\ y'(0) = 12\end{cases}$$

I will show my steps so far.

After taking the transform of each term I get:

$$s^2Y(s) - 2sY(s) + 5Y(s) - 2s - 8 = \frac {-8}{s+1}$$

I simplified the L.H.S and got: $$ Y(s)(s^2-2s+5) = \frac {-8}{s+1} + 2s+ 8 $$

Then the R.H.S becomes:

$$ Y(s)(s^2-2s+5) = \frac {2s^2+10s}{s+1}$$

I then get:

$$Y(s) = \frac {2s^2+10s}{(s+1)(s^2-2s+5)}$$

I then used partial fraction decomposition and got $A = -1, B = 3$, and $C = 5$

I then have the following:

$$Y(s) = \frac {-1}{s+1} + \frac {3s+5}{s^2-2s+5}$$

I am now stuck finding the inverse Laplace transform of the second term.

Please can someone check my work and let me know if I did this right and, if so, what is that inverse Laplace transform I mentioned at the last step?

Help is greatly appreciated. Thank you.


You have $s^2-2s+5=(s-1)^2+4$. So the first term looks like $$ \frac {3s+5}{(s-1)^2+4} =\frac {3(s-1)+8}{(s-1)^2+4} =\frac {3(s-1)}{(s-1)^2+4} +\frac {8}{(s-1)^2+4}. $$ Since $\frac{s}{s^2+4}$ is the transform of $\cos 2t$ and $\frac2{s^2+4}$ of $\sin 2t$, with the shifting rule you get $$ \mathcal L^{-1}\left[\frac {3s+5}{s^2-2s+5}\right] =\mathcal L^{-1}\left[\frac {3s+5}{(s-1)^2+4}\right] =3e^t\cos2t+4e^t\sin 2t $$

  • $\begingroup$ Thank you. Surprised I didn't think to complete the square $\endgroup$
    – the boy 88
    Apr 30 '18 at 4:32

$$\frac {3s+5}{s^2-2s+5}=$$

$$\frac {3s+5}{(s-1)^2+4}=$$

$$\frac {3(s-1)}{(s-1)^2+4} +\frac {8}{(s-1)^2+4}$$

The inverse laplace transform is

$$3e^t\cos 2t +4e^t\sin 2t $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.